2021
DOI: 10.1371/journal.pone.0254205
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib and poziotinib overcome ABCB1-mediated paclitaxel resistance in ovarian cancer

Abstract: Conventional frontline treatment for ovarian cancer consists of successive chemotherapy cycles of paclitaxel and platinum. Despite the initial favorable responses for most patients, chemotherapy resistance frequently leads to recurrent or refractory disease. New treatment strategies that circumvent or prevent mechanisms of resistance are needed to improve ovarian cancer therapy. We established in vitro paclitaxel-resistant ovarian cancer cell line and organoid models. Gene expression differences in resistant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…The findings suggest that paclitaxel insensitivity is associated with the overexpression of both ABCB1 (MDR1) and ABCG2 (BCRP) transporters. This result, on the one hand, is consistent with the literature data [ 46 , 47 ], and on the other, it emphasizes the urgent need to expand the range of efflux proteins studied, compared with the recent idea of P-glycoprotein as the main source of resistance.…”
Section: Resultssupporting
confidence: 91%
“…The findings suggest that paclitaxel insensitivity is associated with the overexpression of both ABCB1 (MDR1) and ABCG2 (BCRP) transporters. This result, on the one hand, is consistent with the literature data [ 46 , 47 ], and on the other, it emphasizes the urgent need to expand the range of efflux proteins studied, compared with the recent idea of P-glycoprotein as the main source of resistance.…”
Section: Resultssupporting
confidence: 91%
“…McCorkle et al cultured seven PDO lines from tumor tissues of seven OC patients. RNA sequencing was then performed to analyze the differences in gene expression between the paclitaxel-sensitive and -resistant organoids, revealing a significant upregulation of the ABCB1 gene in the resistant organoids (McCorkle et al 2021 ). Sun et al established ten PDOs from four platinum-resistant and six platinum-sensitive OC patients’ tumor tissues and identified Aurora-A as a resistant target through RNA sequencing analysis (Sun et al 2020 ).…”
Section: Application Of Patient-derived Oc Organoids In Precision Med...mentioning
confidence: 99%
“…Studies have shown that some other LINC00355 downstream targets promote chemotherapy resistance in cancer. For example, HMGA2 promotes cisplatin resistance in CRC and CC [ 69 , 70 ] and oxaliplatin resistance in CRC [ 71 ]; ABCB1 promotes erastin, docetaxel, and paclitaxel resistance in OC [ 72 , 73 ]; ITGA2 promotes paclitaxel resistance in OC [ 74 ]; WNT10B promotes doxorubicin resistance in TNBC [ 75 ] and cisplatin resistance in CRC [ 76 ]; and CCNE1 promotes platinum resistance in epithelial ovarian cancer, ovarian cancer, and endometrial cancer [ 77 , 78 ].…”
Section: Linc00355‐related Drugs and Potential Drug Resistancementioning
confidence: 99%